Integration of YOLO-RTLite with Wireless Sensor Network ‎Simulation in OMNeT++‎ - Kaur, Manjot; Randhawa, Rajneesh; Kaur, Jagroop (International Journal of Basic and Applied Sciences, 2025)
Real-time decision-making in smart surveillance and traffic management systems requires ‎efficient coordination between visual detection components and wireless sensor networks. In ‎this context, the authors propose an integrated simulation framework that connects YOLO-‎YOLO-YOLO-RTLite-based object detection with a wireless sensor network. The WSN is simulated in ‎OMNeT++, using MQTT as the communication protocol for sending alerts. The system is meant ‎for curved or blind road sections. It uses an object detector on one side to warn vehicles on the ‎other side about oncoming hazards. The framework is evaluated based on metrics such as end-‎to-end delay, throughput, system stability, and alert reliability. Results confirm the system’s ‎ability to function consistently under real-time constraints. A significant contribution of this ‎work is the novel integration of live visual input from YOLO with OMNeT++ simulations, ‎enabling event-driven behavior in WSN triggered by actual object detections‎.